2023
DOI: 10.3390/ani13162682
|View full text |Cite
|
Sign up to set email alerts
|

Effects and Mechanisms of Cage versus Floor Rearing System on Goose Growth Performance and Immune Status

Bincheng Tang,
Shenqiang Hu,
Xin Zhang
et al.

Abstract: Currently, FRS and CRS are the two predominant dryland rearing systems in the goose industry. However, the effects of these two systems on goose growth performance and health, as well as the underlying mechanisms, have not been fully clarified. Thus, this study aimed to compare growth performance and immune status, as well as investigate the genome-wide transcriptomic profiles of spleen in geese, between CRS and FRS at 270 d of age. Phenotypically, the body weight and body size traits were higher in geese unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
(40 reference statements)
0
1
0
Order By: Relevance
“…The GO enrichment analysis showed that the DEGs identified in spleens of each goose breed between different weeks of age were mostly enriched in the terms related to organ morphogenesis and development, such as nucleus and extracellular space. Similarly, several previous studies have reported that the age has major effects on the development of the goose spleen by regulating cell differentiation ( 31 , 32 ). Besides, the DEGs identified in spleens of the same age between two goose breeds were mostly enriched in the GO terms related to the structure and ion transport of plasma membrane.…”
Section: Discussionmentioning
confidence: 52%
“…The GO enrichment analysis showed that the DEGs identified in spleens of each goose breed between different weeks of age were mostly enriched in the terms related to organ morphogenesis and development, such as nucleus and extracellular space. Similarly, several previous studies have reported that the age has major effects on the development of the goose spleen by regulating cell differentiation ( 31 , 32 ). Besides, the DEGs identified in spleens of the same age between two goose breeds were mostly enriched in the GO terms related to the structure and ion transport of plasma membrane.…”
Section: Discussionmentioning
confidence: 52%